A Facile Approach to Improve Interchain Packing Order and Charge Mobilities by Self‐Assembly of Conjugated Polymers on Water. Issue 11 (9th October 2018) - Yang, Yizhou; Liu, Zitong; Chen, Jianmei; Cai, Zhengxu; Wang, Zhijie; Chen, Wei; Zhang, Guanxin; Zhang, Xisha; Chi, Lifeng; Zhang, Deqing
Abstract: Development of facile and economic approaches for assembling organic semiconductors into more ordered structures toward high charge mobilities is highly demanding for the fabrication of organic circuits. Here a simple and facile approach is reported to prepare conjugated polymer thin films with improved crystallinities and charge mobilities by self‐assembling semiconducting polymers on water. The formation of polymer thin films with more ordered structures is attributed to coffee ring effect induced by solvent‐evaporation on water, and the hydrophobic nature of conjugated polymers that forces the polymer chains to pack densely and orderly on water surface. This approach is applicable to typical semiconducting polymers, and charge mobilities of their thin films are boosted remarkably. Finally, this new method can be utilized to easily fabricate the array of field‐effect transistors with high charge mobilities in an economic way. Abstract : A unique and facile approach is reported to prepare conjugated polymer thin films with improved crystallinities by assembling semiconducting polymers on water (AOW), by using synergic actions of "coffee‐ring" effect and the hydrophobic feature of conjugated polymers. This AOW approach is generally applicable to several conjugated polymers, which can improve their semiconducting properties significantly.